2018
DOI: 10.4314/gjpas.v24i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with malnutrition among underfive children in developing countries: A review

Abstract: Malnutrition is a consequence of consumption of dietary nutrient either insufficiently or exclusively by especially children. The aim of this study was to carry out a review of malnutrition-dependent factors among under-five children in developing countries. The study was carried out by reviewing publications on researches on malnutrition conducted in Africa and Asia with particular reference to factors associated with malnutrition. It was found that, of the 162 million children under five years who were stunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 27 publications
3
35
1
4
Order By: Relevance
“…Overall, developing countries had an estimated 60 million under five stunted children [12]. it was also observed that wasting increased from 11% in 2003 to 18% in 2013, underweight from 24% in 2003 to 29% in 2013 while stunted decrease from 42% in 2003 to 37% in 2013 [12]. The rate of malnutrition is a serious source of concern and also due to its potential effect in the later years of children.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, developing countries had an estimated 60 million under five stunted children [12]. it was also observed that wasting increased from 11% in 2003 to 18% in 2013, underweight from 24% in 2003 to 29% in 2013 while stunted decrease from 42% in 2003 to 37% in 2013 [12]. The rate of malnutrition is a serious source of concern and also due to its potential effect in the later years of children.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the most cited research publications, some of the most prominent authorship and institution were from the United States, England, and Denmark. While recent evidence has identified that most recent global malnutrition cases are prevalent in developing countries [46,47], only Kenya and Bangladesh were among the top authors globally. This exposition suggests a significant dearth of authorship coming from the developing countries represented in the web of science databases.…”
Section: Discussionmentioning
confidence: 99%
“…Mother's occupation was associated with underweight and stunting in this study. Nutritional and health status of children can be severely affected by their mothers' occupation (Abbir et al, 2006) possibly because the care needed by the children from working-class mothers may be hindered due to time constraints (Kalu and Etim, 2018).…”
Section: Discussionmentioning
confidence: 99%